Photocommunication across media : beginning photography for professionals in mass media - Collins, Ross F.; Greenwood, Keith, 1962- (Routledge, 2018)
"Photocommunication Across Media is a must-have for aspiring mass media professionals who are striving to compete in the new landscape of convergence journalism and media. You will learn principles of photography both still and video and how to incorporate them into your storytelling. That's no longer a specialty skill--in today's world of media, it's a necessity. Editors Ross Collins and Keith Greenwood collaborate with highly accomplished photographers to make the concepts and techniques of today's mass media photography accessible to all readers. Photocommunication Across Media speaks directly to journalists, advertisers and professional communicators who want to round out their toolkit without sifting through dense texts meant specifically for photographers and photojournalists. This guide, edited by experts who teach these concepts to the next generation of media professionals, is everything you need to know--and nothing you don't--to take the next step for your career in communication."--Provided by publisher